Dental extraction in patients on warfarin treatment: a series of 35 patients - Abdullah WA; Khalil H (Dove Medical Press, 2014)
Walid Ahmed Abdullah,1,2 Hesham Khalil1 1Department of Oral and Maxillofacial Surgery, College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2Department of Oral and Maxillofacial Surgery, College of Dentistry, Mansoura University, Mansoura, Egypt Background: Warfarin is one of the most common oral anticoagulants used to prevent thromboembolic episodes. The benefits of discontinuation of this drug before simple surgical procedures are not clear and this approach could be associated with complications. The aim of this study was to evaluate the risk of bleeding in a series of 35 patients (in cases where the international normalized ratio [INR] is less than 4) following simple tooth extraction without modification of the warfarin dose given to patients. Methods: Thirty-five patients taking warfarin who had been referred to the Oral and Maxillofacial Department, College of Dentistry, King Saud University, for dental extractions were included in the study. Exclusion criteria included patients with an INR of ≥4 or with a history of liver disease or coagulopathies. No alteration was made in warfarin dose, and the CoaguChek System was used to identify the INR on the same day of dental extraction. Bleeding from the extraction site was evaluated and recorded immediately after extraction until the second day. Results: A total of 35 patients (16 women and 19 men) aged between 38 and 57 years (mean =48.7) were included in the present study. All patients underwent simple one-tooth extraction while undergoing warfarin treatment. Oozing, considered mild bleeding and which did not need intervention was seen in 88.6% of patients. Moderate bleeding occurred in 11.4% of all cases. The INR of the patients ranged from 2.00 to 3.50, with 77.2% of patients having INR between 2.0 and 2.5 on the day of extraction. No severe bleeding which needed hospital management was encountered after any of the extractions. The patients who suffered moderate bleeding were returned to the clinic where they received local treatment measures to control bleeding. Moderate bleeding occurred only in four patients, where three had INR between 3.1 and 3.5, and one with INR less than 3. Conclusion: In the present study, we have shown that simple tooth extraction in patients on warfarin treatment can be performed safely without high risk of bleeding, providing that the INR is equal or less than 3.5 on the day of extraction. A close follow-up and monitoring of patients taking warfarin is mandatory after dental extraction. Keywords: tooth extraction, bleeding, INR